2021
DOI: 10.3389/fcell.2021.730558
|View full text |Cite
|
Sign up to set email alerts
|

PPA1 Promotes Breast Cancer Proliferation and Metastasis Through PI3K/AKT/GSK3β Signaling Pathway

Abstract: Breast cancer is the most common malignancy among women. Inorganic pyrophosphatase 1 (PPA1) is a multifunctional protein involved in the development of several tumors. However, the role of PPA1 in breast cancer progression remains unclear. In this study, we found that PPA1 was highly expressed in breast cancer compared to its levels in normal breast tissue and that it was correlated with breast cancer clinicopathological characteristics, as well as poor survival in breast cancer patients. Silencing PPA1 restra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This resulted in the conformational variations at the PI3K receptor and the follow-up recruitment phosphorylation. Following activation, PI3k induced the activation of a core signaling kinase Akt, which controls some downstream effector molecules like glycogen synthase kinase-3β (GSK3β), driving protein and lipid synthesis, and cell development [ 51 , 52 ]. It also induced the activation of the forkhead box O (FOXO) family, which participates in various cellular physiological processes and regulates cell proliferation, cell cycle [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in the conformational variations at the PI3K receptor and the follow-up recruitment phosphorylation. Following activation, PI3k induced the activation of a core signaling kinase Akt, which controls some downstream effector molecules like glycogen synthase kinase-3β (GSK3β), driving protein and lipid synthesis, and cell development [ 51 , 52 ]. It also induced the activation of the forkhead box O (FOXO) family, which participates in various cellular physiological processes and regulates cell proliferation, cell cycle [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PPA1 on JNK dephosphorylation also induces type I collagen synthesis and stimulates calcification of osteoblasts (38). Furthermore, PPA1 has been shown to play a vital role in mediating tumor proliferation, apoptosis, and metastasis in a JNK activation-dependent or -independent manner; this is discussed in detail below (13,14,17).…”
Section: Biological Functions Of Ppa1mentioning
confidence: 99%
“…The phosphatidylinositol 3-kinase (PI3K) and its downstream molecule AKT serine/threonine kinase (AKT), have been shown to be closely associated with tumor EMT, and activation of PI3K/AKT leads to the inhibition of epithelial characteristics and expression of mesenchymal proteins (45,46). Guo et al found that PPA1 acts as an activator of the PI3K/AKT/ GSK-3b pathway and participates in the development of EMT induced by transcription factor Slug, thereby promoting breast cancer proliferation and metastasis (17). However, PPA1 is not directly upstream of PI3K, and their molecular interactors have not yet been reported.…”
Section: Regulation Of Emt Via Pi3k/akt/gsk-3b Signalingmentioning
confidence: 99%
See 2 more Smart Citations